Be(com)ing an Asian tangata tiriti - Lincoln Dam (Kōtuitui, 2023)
ABSTRACTIn Aotearoa-New Zealand, talk of Te Tiriti o Waitangi (the Treaty of Waitangi, New Zealand’s foundational colonial contract) often centres on Indigenous Māori and Pākehā (New Zealanders of European descent) relations. But, as an Asian New Zealander, where do our Asian (im)migrants/communities fit into such discussions? What are our responsibilities to Māori, the Indigenous people of the land, and Te Tiriti? How might wisdom inherited from our ancestors, in particular, Asian philosophies, help us to think through these questions? Here, I document my journey hitherto of be(com)ing an Asian tangata tiriti – a person/people group belonging here via Te Tiriti. I critically reflect on my (family’s) story and struggles with (not) belonging as Asians in Aotearoa-New Zealand. Learning from te ao Māori (the Māori world), I then reach for wisdom inherited from my own ancestors. I demonstrate how Chinese, Thai and Theravāda Buddhist philosophies on relationality and ethics teach me to live a virtuous life with others and, by extension, to have good, productive relationships with Māori and Te Tiriti. This paper creates possibilities for other (Asian) (im)migrants to reimagine their relationships with Indigenous peoples and treaties here, and elsewhere, and to be(come) tangata tiriti (or equivalent) too.